The Role of Licensing in the Strategy of Western Firms in the Eastern European Markets: The Case of Poland - Ryszard Rapacki (World Economy Research Institute, 1986)
The aims of this paper are to examine the role of licensing in the strategy of Western firms aimed at increasing their share in East European markets and to establish the pattern of their licensing policy pursued there. It is also expected that, as a by-product of this study, some other important features of East-West trade in licenses will be found out.
Keywords: O33; O34; 330; East-West trade; licenses; international trade; licenses